Análisis del régimen impositivo para Microempresas del Ecuador y su incidencia en la determinación Tributaria. - Silva Aguayo, Melissa Rebeca (2021)
The Organic Law of Tax Simplification and Progressivity 2019 incorporates “Tax Regime for Micro-enterprises” generating confusion for the taxpayer, because of the Tax Administration issued the cadaster’s taxpayers to the regime without considering the necessary analysis for their categorization. The implementation of the Tax Regime for Microenterprises has generated inconveniences for the taxpayer in its application, such as: (a) difficulties in the tax determination due to the conceptual difference of the taxable base for the Income Tax in the Law and the Regulations, (b) cadaster issued by the Tax Administration includes the taxpayers limited to the regime, (c) the regulations of the tax regime for micro-businesses and related laws add complexity to the tax determination and the formal duties of the taxpayer. This research analyzes the Tax Regime for Microenterprises of Ecuador and its incidence in the Tax Determination, in which the factors that generate confusion for the taxpayer in the determination of their tax obligations are identified.